(untitled) (Scottish Historical and Archaeological Internet Reports, 2005)
The excavation of the Geodha Smoo cave complex resulted in the recovery of numerous archaeological deposits containing well-preserved artefactual and environmental evidence. The deposits clearly indicate the importance of this coastal location in the past. The deposits in the Wetweather Cave indicate prehistoric activity, but most of the evidence, from all the other caves, indicate their use during the Viking, Late Norse and post-Norse periods.